2008
DOI: 10.1016/j.addbeh.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alternative forms of tobacco use in a population of young adult military recruits

Abstract: Recent evidence suggests that the popularity of certain alternative forms of tobacco may be increasing in adolescents. Little is known, however, about the use of these products among young adults. This study examined the use of alternative tobacco products including bidis, cigars, kreteks (clove cigarettes), pipes, and smokeless tobacco in a large sample of young adult military recruits (N=31107). Overall, 18.5% of participants were using some form of alternative tobacco product prior to entry into Basic Milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…Previous studies have suggested nontrivial rates of combined smoking and smokeless tobacco use in youth ( Severson, Forrester, & Biglan, 2007 ) and young adults in the military ( Vander Weg et al, 2008 ), and one study has indicated that among military personnel, high rates of smokeless tobacco use were observed particularly among those smoking fewer than 10 cpd ( Peterson et al, 2007 ). The current results indicate that more smokeless tobacco use is associated with less smoking.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have suggested nontrivial rates of combined smoking and smokeless tobacco use in youth ( Severson, Forrester, & Biglan, 2007 ) and young adults in the military ( Vander Weg et al, 2008 ), and one study has indicated that among military personnel, high rates of smokeless tobacco use were observed particularly among those smoking fewer than 10 cpd ( Peterson et al, 2007 ). The current results indicate that more smokeless tobacco use is associated with less smoking.…”
Section: Discussionsupporting
confidence: 63%
“…Next, history of tobacco use was assessed, including the use of cigarettes, smokeless tobacco, cigars, pipes, clove cigarettes, and bidis. For the present study, however, we limited our focus to smokeless tobacco and cigars as these two products are the most commonly used among this population ( Vander Weg et al, 2008 ). The smoking categories included never-smokers (never smoked, not even a puff), experimental smokers (smoked on only one to two occasions), former smokers (smoked at least 1 cpd regularly but had quit in the past 6 months, quit between 6 months and 1 year ago, and quit more than 1 year ago), and regular smokers (smoked regularly up to the beginning of BMT).…”
Section: Methodsmentioning
confidence: 99%
“…Smoking is the most common method of tobacco intake and occurs via the use of cigarettes, cigars, pipes, kreteks, bidis, and narghile. The habit of pipe smoking is becoming less common, 43 but cigar smoking is increasingly popular and it is cautionary to note that cigars contain signifi cantly higher concentrations of toxic and carcinogenic compounds than cigarettes. 44 Bidis are small, brown, hand-rolled tobacco cigarettes rolled in tendu or temburni leaves and usually tied with a string at one end; they are primarily used in India and South East Asia.…”
Section: Narghile and Oral Cancermentioning
confidence: 99%
“…44 Bidis are small, brown, hand-rolled tobacco cigarettes rolled in tendu or temburni leaves and usually tied with a string at one end; they are primarily used in India and South East Asia. 43 Kreteks are cigarettes with a blend of tobacco and cloves/ oil of cloves; they contain approximately 60% tobacco and 40% ground clove buds and have a distinctive scent. 43,45 The risks of smoking tobacco, however, are signifi cantly compounded by 'reverse' smoking whereby the lighted end of a cigarette is placed within the oral cavity, a habit that is popular in South America.…”
Section: Narghile and Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation